Detection of Oral Entamoeba Gingivalis in a Kut Population with Gingivitis and Periodontal disease - Teba malik Khudair abbas; Mahmood Hussein Hamza Hammoud; Mustafa Ahmad Thanoon Yahya; Farah deyaa hamza Hassan; Haneen Adi Aref Ebadi (Genius Journals, 2024)
With regard to the parasitological confirmation, E. gingivalis trophozoites were evident microscopically within all 22 positive specimens.The study involved 30 persons: 15 women and 15 men. In the studied group. The study consisted of the observation of samples derived by way of buccal swabs under a microscope in a search for Entamoeba gingivalis trophozoites. Such protozoa were found in 22 patients, but no in 7 patients . Among the samples derived from women, the protozoa were in 13 (59.09%), and among men, in 9 subjects (40.91%).It was found during the examination that the percentage of non-smoking individuals was the highest, 95.54%, and the lowest percentage of smoking individuals was 4.55%. The number. The total number of people examined was N = 30.Out of 30 investigated studies, 30 specified a mean age for their sample size. Results showed an increase in prevalence on (21-30) the age of the patients, the lowest prevalence was reported lass 10 age and (51-60) age
Keywords: Entamoeba Gingivalis; Periodontal disease; women